Network Pharmacology Reveals the Mechanism of Activity of Tongqiao Huoxue Decoction Extract Against Middle Cerebral Artery Occlusion-Induced Cerebral Ischemia-Reperfusion Injury - Wu, Si-peng; Wang, Ning; Zhao, Li (Frontiers in Pharmacology, 2021)
Some clinical therapies such as tissue repair by replacing injured with functional tissues have been reported, yet there is the great explore potential for traditional herbal-induced regeneration with good safety. Tongqiao Huoxue Decoction (TQHXD), a well-known classical traditional Chinese Medicinal formula, has been widely used for clinical treatment of stroke. However, biological activity and mechanisms of action of its constituents towards conferring protection against cerebral ischemia reperfusion (I/R) injury remain unclear. In this present study, we evaluated TQHXD quality using HPLC, then screened for its potential active ingredients using a series of indices, such as their drug-likeness and oral bioavailability. Subsequently, we analyzed the potential mechanisms of TQHXD anti-I/R using gene ontology functional enrichment analyses. The network pharmacological approach enabled us to screen 265 common targets associated with I/R, indicating that TQHXD had remarkable protective effects on infarction volume, neurological function scores and blood-brain barrier (BBB) injury. In addition, TQHXD significantly promoted recovery of regional cerebral blood flow (r CBF) 7 days after reperfusion, relative to rats in the vehicle group. Immunofluorescence results revealed a significantly higher CD 34 expression in TQHXD treated rats, 7 days after reperfusion. TQHXD is not merely effective, but eventually develops a secretory profile composed of VEGF and cerebral blood flow, a typical signature termed the angiogenesis-associated phenotype. Mechanistically, our data revealed that TQHXD (6 g/kg) treatment resulted in a marked increase in expression of p-Focal Adhesion Kinase (FAK) and p-Paxillin proteins. However, Ki8751-mediated inhibition of VEGFR2 activity repealed its angiogenesis and protective effects, and decreased both p-FAK and p-Paxillin protein levels. Taken together, these findings affirmed the potential for TQHXD as a drug for management of stroke, which might be exerted by increasing the angiogenesis via the VEGF pathway. Therefore, these results provide a proof of concept evidence that angiogenesis is a major contributor to TQHXD-treated I/R and that TQHXD is a promising traditional ethnic medicine for management of this condition.